Perbandingan Pengaturan Eksekusi Pidana Mati di Indonesia dan Vietnam: Comparison of the Implementation of the Death Penalty in Indonesia and Vietnam - Zefanya Christina Iustitia; Gandes Candra Kirana (Reformasi Hukum Trisakti, 2025)
Throughout history, law has played a crucial role in ensuring security, peace, justice, and societal prosperity. The death penalty remains a controversial topic due to its impact on human rights. In Indonesia, despite significant opposition and calls to respect the right to life, it is still applied for serious crimes such as murder and drug offenses. This study addresses the similarities and differences in death penalty execution regulations and analyzes their strengths and weaknesses in Indonesia and Vietnam. This normative legal research relies on secondary data analyzed qualitatively using a deductive method. The result and conclusion is that there are significant differences in regulation and implementation practices. In Indonesia, the death penalty is carried out under strict procedures but often faces criticism regarding the transparency and fairness of the process. Meanwhile, Vietnam adopts a method of execution that is considered more humane, but faces criticism regarding the lack of transparency and potential human rights violations.